Socjotechnika i jej konsekwencje w wyborach samorządowych z 2014 roku – przykłady wybranych miast województwa małopolskiego - Pasiut, Judyta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The target of the analysis of this thesis is the social engineering’ techniques and methods used by politicians during the local election campaign in the Malopolska voivodeship in 2014. The article includes selected examples of various election activities, which could be observed in different cities throughout the region. The examination of the thesis embodied those practices, the main purpose of which is to gain trust and support from the electorate, as well as those activities which have unethical and unfair character. Moreover, the media’s participation in the campaign and their influence on the electorate has been analyzed. The article includes the answer to the question: what influence had involvement of social engineering techniques during the election campaign on local communities and candidates?
Social engineering in the 2014 local elections – examples of selected cities of malopolska voivodeship
Keywords: social engineering; local elections; politics